Buoyancy Versus Local Stress Field Control on the Velocity of Magma Propagation: Insight From Analog and Numerical Modelling - Pinel, Virginie; Furst, Séverine; Maccaferri, Francesco; Smittarello, Delphine (Frontiers in Earth Science, 2022)
Magmatic dykes interact with heterogeneous crustal stress. As a result, their propagation towards the surface can be tortuous and their propagation velocity may vary. While the deflection of dykes in response to the local stress field has been addressed by several studies, less has been done about the effect on their propagation velocity. Understanding under which conditions an intrusion may accelerate or decelerate due to crustal stress heterogeneities has obvious important implications in terms of forecasting the timing of the onset of the eruption. Here we analyse the velocity of fluid-filled crack propagation in a gelatin block characterized by a heterogenous stress field considering the case study of a load applied at the surface. We find that a crack deflected towards the load and its underlying compressive stress field is decelerated. By comparing experimental results with numerical solutions, we evidence the potential complementary role played by stress field variations and changes in trajectory orientation, controling the buoyancy, on the velocity of magma propagation. We also show that the energy release estimated along the crack path by simplified numerical models appears to be a good proxy for the velocity. We conclude that numerical models allowing for magma path estimations, could also be used to infer magma velocity variations. In addition, 1D numerical models solving for the fluid flow along a prescribed path, provide velocity variation as a function of the surrounding stress field and the magma driving pressure.